Promoting Environmentally Friendly Economic Behavior Through Education: A Strategy for Achieving Sustainable Development - Rima Handayani; Bayu Dwi Hatmoko; Afifatus Solihah; Ininis Novita Rani (Journal of Social Studies Education and Humanities Research, 2025)
This study aims to examine and analyze the role of education, particularly economic education, in shaping environmentally friendly economic behavior of students as a strategy to realize sustainable development. This study uses a descriptive qualitative approach based on a literature review that examines national, international scientific sources, and official documents. The results of the review show that economic education has significant potential to instill sustainability values through sustainable economic literacy. This literacy includes students’ ability to understand, evaluate, and make economic decisions that consider social and ecological impacts. However, in practice, economic learning in schools is still focused on the cognitive level and has not fully integrated sustainability values comprehensively. In addition, environmentally friendly economic behavior has also not become a primary indicator in learning outcomes, thus creating a gap between the competencies developed and the expected sustainability goals. This study finds that the number of studies that examine changes in economic behavior as an indicator of the success of sustainable economic education is still very limited. This opens the door for further research focusing on the relationship between economic education, sustainable economic literacy, and the formation of economic behavior that is aware of ecological aspects